2014
DOI: 10.1111/are.12526
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, growth and nutrient retention of common sole (Solea soleaL.) fed natural prey and an artificial feed

Abstract: This study compares growth, intake and retention efficiencies of nutrients and energy between common sole (Solea solea L.) fed ragworm (Nereis virens, Sars), blue mussel (Mytilus edulis L.) and an artificial (commercial) feed. Food types were fed to common sole (mean initial body weight: 44.9 ± 2.3 g) in excess three times a day over a 54‐day‐period. The growth rate in common sole fed the natural prey (8.5 g kg−0.8 d−1) was significantly higher compared to the growth rate in fish fed the artificial feed (5.1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Fonds, Drinkwaard, Resink, Eysink and Toet () and Ende et al . () showed that the growth of sole fed mussel is comparable to the growth of sole fed ragworm. We, therefore, expect that also mussel will alleviate anaemia in sole, consequently showing comparable levels of haematocrit (Hct) and haemoglobin (Hb) for sole fed mussel or ragworm, but higher for sole fed pellet.…”
Section: The Proximate Composition Iron and Vitamin B12 Content Of Tmentioning
confidence: 96%
See 1 more Smart Citation
“…Fonds, Drinkwaard, Resink, Eysink and Toet () and Ende et al . () showed that the growth of sole fed mussel is comparable to the growth of sole fed ragworm. We, therefore, expect that also mussel will alleviate anaemia in sole, consequently showing comparable levels of haematocrit (Hct) and haemoglobin (Hb) for sole fed mussel or ragworm, but higher for sole fed pellet.…”
Section: The Proximate Composition Iron and Vitamin B12 Content Of Tmentioning
confidence: 96%
“…Common sole grows approximately 70% faster on ragworm than on commercial pellets (Ende, Kroeckel, Schrama, Schneider & Verreth ), the latter causing them to suffer from nutritional anaemia (Kals, Blonk, Palstra, Sobotta, Mongile, Schneider, Planas, Schrama & Verreth submitted). Changing the diet from pellet to ragworm alleviates this nutritional anaemia (Kals, Blonk, van der Mheen, Schrama & Verreth ).…”
Section: The Proximate Composition Iron and Vitamin B12 Content Of Tmentioning
confidence: 99%
“…Recently, Ende et al. () showed a better growth in common sole juveniles fed fresh mussel in comparison with commercial dry feed, suggesting the use of mussels as a reference feed for this species. However, in that study, mussels were not used as a dry feed ingredient and the differences in the physical and chemical composition between the two sources of feed may have influenced palatability, feed intake and growth.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of unconventional protein and lipid sources able to mimic the organoleptic characteristics of the sole's natural feed would be of particular interest for exploring the growth potential of this species using dry feed (Parisi et al, 2014). Recently, Ende et al (2014) showed a better growth in common sole juveniles fed fresh mussel in comparison with commercial dry feed, suggesting the use of mussels as a reference feed for this species. However, in that study, mussels were not used as a dry feed ingredient and the differences in the physical and chemical composition between the two sources of feed may have influenced palatability, feed intake and growth.…”
Section: Introductionmentioning
confidence: 99%
“…feed intake, feed efficiency and growth) of sole. Ende, Kroeckel, Schrama, Schneider and Verreth () found that common sole grew ±70% faster on ragworm than on a commercial feed.…”
Section: Introductionmentioning
confidence: 99%